Support for association between ADHD and two candidate genes: NET1 and DRD1 (2005)
ABSTRACT: Attention deficit hyperactivity disorder (ADHD)is a common, multifactorial disorder with signifi-cant genetic contribution. Multiple candidategenes have been studied in ADHD, including thenorepinephrine transporter (NET1) and dopa-mine D1 receptor (DRD1). NET1 is implicated inADHD because of the efficacy of atomoxetine, aselective noradrenergic reuptake inhibitor, in thetreatment of ADHD. DRD1 is primarily implicatedthrough mouse models of ADHD. DNA from 163ADHD probands, 192 parents, and 129 healthycontrols was used to investigate possible associa-tions between ADHD and polymorphisms in 12previously studied candidate genes (5-HT1B,5-HT2A,5-HT2C,ADRA2A,CHRNA4,COMT,DAT1,DRD1,DRD4,DRD5,NET1, andSNAP-25). Ana-lyses included case-control and family-basedmethods, and dimensional measures of behavior,cognition, and anatomic brain magnetic reso-nance imaging (MRI). Of the 12 genes examined,two showed a significant association with ADHD.Transmission disequilibrium test (TDT) analysisrevealed significant association of two NET1single nucleotide polymorphisms (SNPs) withADHD (P 0.009); case-control analysis revealedsignificant association of two DRD1 SNPs withADHD (P 0.008). No behavioral, cognitive, orbrain MRI volume measurement significantlydiffered across NET1 or DRD1 genotypes at analpha of 0.01. This study provides support for anassociation between ADHD and polymorphismsin both NET1 and DRD1; polymorphisms in tenother candidate genes were not associated withADHD. Because family-based and case-control methods gave divergent results, both should beused in genetic studies of ADHD.